Pengaruh Pengetahuan Kewirausahaan dan Self Efficacy Terhadap Kesiapan Berwirausaha pada Mahasiswa di Kota Sukabumi - M Yaumal Mizan Firdaus; R Deni Muhhammad Danial; Resa Nurmala (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
In the context of globalization which is currently very strong, the availability of a large workforce but the number of jobs and employment opportunities is small is the main factor causing employment problems, including unemployment. Every individual has the same goal, namely having optimal work readiness, which will influence positive work results for the success of their business. That way each individual will achieve the desired goal. The aim of this research is to determine the description of entrepreneurial knowledge, self-efficacy and entrepreneurial readiness among students in Sukabumi City. The sampling technique in this research used purposive sampling, the samples taken in this research were 300 students. Based on the research results, it shows that there is a positive and significant influence between entrepreneurial knowledge and self-efficacy on entrepreneurial readiness.